Study of thermal maturation processes of sulfur-rich source rock using compound specific sulfur isotope analysis. (October 2017) - Rosenberg, Yoav O.; Meshoulam, Alexander; Said-Ahmad, Ward; Shawar, Lubna; Dror, Guy; Reznik, Itay J.; Feinstein, Shimon; Amrani, Alon
Highlights: Organic sulfur compounds (OSC) were evaluated in source rock artificial maturation. δ 34 S of OSC in the oil phase provide insight to the chemical structure of kerogen. Diagenesis and catagenesis tends to lower the variability in the δ 34 S of the OSC. Depletion in the δ 34 S of the H2 S is small and not concurrent with δ 34 S of OSC. The δ 34 S of the OSC is used for oil-source rock correlation on crude oil samples. Abstract: Semi-open pyrolysis experiments were conducted on a thermally immature, organic and sulfur-rich source rock (Ghareb Formation, Israel). Structural and sulfur isotope ratio ( 34 S/ 32 S) changes in specific organic sulfur compounds were studied along with bulk sulfur phases (H2 S, kerogen, oil) during thermal maturation and oil formation. Oil, gas and rock samples were collected sequentially at several points along the maturation path and were analyzed. In addition, four natural crude oils from Israel were analyzed and the results were compared to the pyrolytic oils. The results showed relatively large δ 34 S variability (∼10‰) of the organic sulfur compounds (OSCs) in the bitumen of the unheated rock and first pyrolytic oil. This variability was probably a remnant of the original sulfur isotopic signature acquired during the sulfurization of the organic matter in the early diagenetic process. At later stages of thermal maturation, the variability of the sulfur isotopic values in the kerogen gradually decreased to ∼2‰. Three mechanisms were suggested to explain the structural changes and isotopic fractionations of OSCs in the kerogen and generated oils: (A) Cleavage of weak SS and CS bonds leading to the release of large amounts of H2 S and to cyclization of the precursors in the kerogen with small fractionations. Thus, the OSCs released by this mechanism preserved their distinct δ 34 S values. (B) Re-reaction of the released S species with hydrocarbons and generation of new OSCs within the kerogen (or bitumen) matrix. (C) Cleavage of stronger CC bonds and transformation of OSCs to create more stable compounds (e.g. dibenzothiophenes) from multiple sulfur sources. Mechanisms (B) and (C) homogenized the δ 34 S values of the different OSCs which reflected that of the bulk kerogen. The bulk organic sulfur phases (bitumen, oil, kerogen) were 34 S enriched by < 1‰ despite large amounts of 34 S-depleted H2 S (53% of total S) that was released continuously ("open system"). Therefore, the preferential loss of H2 S during thermal maturation may not be responsible to the 34 S enrichment of oils as reported in some petroleum basins. The overall outcome of the maturation process yields OSCs with δ 34 S values that closely reflect the kerogen and can be used as a fingerprint for oil-oil and oil-source rock correlation over wide ranges of thermal maturity. The applicability of such correlation is demonstrated by the very good correlation of δ 34 S values of specific OSCs between artificial and natural oil samples.